Genetic resistance of common bean cultivar Beija Flor to Colletotrichum lindemuthianum - João Ricardo Silva Marcon; Maria Celeste Gonçalves Vidigal; Jean Fausto Carvalho Paulino; Pedro Soares Vidigal Filho; Marcela Coêlho (Acta Scientiarum. Agronomy, 2020)
Anthracnose, which is caused by the fungus Colletotrichum lindemuthianum, is one of the most widespread and important diseases of the common bean (Phaseolus vulgaris L.) in the world. The objective of the present study was to characterize the genetic resistance of the Beija Flor cultivar by inheritance and to conduct allelism tests. The inheritance test was conducted in the F2 population derived from the Beija Flor (resistant) x TU (susceptible) cross inoculated with race 2047 of C. lindemuthianum. Furthermore, allelism tests exhibited a fitted segregation ratio of 15R:1S, thereby indicating the independence of the Beija Flor gene from the following previously characterized genes: Co-1, Co-2, Co-4, Co-42, Co-6, Co-12, Co-14, Co-15, and Co-Pe. Based on the aforementioned results, we are proposing the symbol Co-Bf to designate the new anthracnose resistance gene in the Brazilian Andean common bean cultivar Beija Flor. This cultivar is an important source of resistance to C. lindemuthianum that should provide a valuable contribution to the common bean breeding program for anthracnose resistance.